PERSEPSI KEPUASAN PASIEN TERHADAP KUALITAS PELAYANAN KESEHATAN DI PUSKESMAS CANGKUANG - Robbani, Istiana; Lukitasari, Lenni (UM. Bengkulu, 2025)
The quality of health services is an important factor in determining the level of patient satisfaction. This study aims to analyze the perception of patient satisfaction with the quality service at Cangkuang Health Center Bandung Regency using the SERVQUAL approach which includes five main dimensions, that is Tangibles, Reliability, Responsiveness, Assurance, Empathy. The research method used is descriptive qualitative, with data collection techniques through observation, interviews, and documentation. Respondents in this study were patients who received services at the Cangkuang Health Center. The research results show that in general patients are quite satisfied with the services provided, but there are also several aspects that need to be repaired and improved to achieve more optimal patient satisfaction. Keywords: Patient Perception, Patient Satisfaction, Quality of Health Services